Analysis of U.S., Kenyan, and Finnish Discourse Patterns in a Cross-Cultural Digital Makerspace Learning Community Through the IBE-UNESCO Global Competences Framework - Danielle P. Espino; Seung B. Lee; Lauren Van Tress; Toby T. Baker; Eric R. Hamilton (Research in Social Sciences and Technology, 2020)
In 2017, the International Bureau of Education (IBE) at the United Nations Educational, Scientific and Cultural Organization (UNESCO) put forth seven global competences to address accelerating technological progress and increasing levels of complexity and uncertainty affecting many facets of society (Marope, 2017). These competences were used in examining participant discourse in a global, collaborative digital makerspace environment, where students ages 12 to 17 from six countries develop and share STEM-focused media artifacts. The participants communicate synchronously through video conference calls, referred to as online global meet-ups. The meet-ups allow students to present media artifacts they have created, share ideas, exchange information, and provide feedback. In this analysis, epistemic network analysis (ENA), a technique in quantitative ethnography, is used to examine the connections made among the IBE-UNESCO global competences in a meet-up involving participants from Finland, Kenya, and the U.S. ENA network models were created initially for the three sites, then further disaggregated by time segment to analyze how participant discourse patterns may have evolved in each context. Through this approach, the paper explores more broadly the interactive role of media making, cross-cultural engagement, and collaborative learning in the development of global competences in students.